Understanding outreach: the potential of qualitative longitudinal research to enrich the evidence base. (20th November 2020) - Raven, Neil
Recent calls from the Office for Students, the regulatory body for the English higher education sector, have challenged those engaged in widening university access to 'strengthen' the outreach evidence base. Whilst focus groups have proved capable of revealing much about the learner experience and the effectiveness of outreach interventions, the established way in which they have been applied – in capturing views and perceptions at one particular point in time – limits what can be discovered. Adopting a longitudinal approach in the application of this research instrument – by returning to the same group of participants at regular intervals over a number of months – affords a chance to monitor changes in ideas and intentions, and distinguish the important from the fleeting. As the findings from three recent studies that have deployed this approach show, it can also generate richer, more detailed insights than would otherwise be possible.